Pengaruh Model Childrean Learning in Science (CLIS) Terhadap Kemampuan Berfikir Kritis Siswa di UPT SDN 207 Gresik - Sa'diyah; Ria Resti Fauziah (El-Miaz: Jurnal Pemikiran dan Pendidikan Dasar, 2024)
This research aims to find out: Is there an influence of ability Critical Thinking Students taught using the Children Learning in Science (CLIS) model in learning science and science on the topic of magnetic force. Critical thinking is to include judgment or careful evaluation, such as assessing the suitability of an idea or product. Muhibbin identifying rational thinking and critical thinking are manifestations learning behavior, especially those related to solutions to these problems. Matter It is understood that students have critical thinking skills use basic principles and foundations of understanding to answer questions, such as "how" (how) and "why" (why). Terms Critical thinking too It requires students to use several appropriate cognitive strategies to test ideas troubleshoot and resolve errors or deficiencies. Hence this research aims to determine the effect of using the Children Learning in Science model (CLIS) on the critical thinking abilities of UPT SDN 207 Gresik students. Types of research This is quantitative using pre-experimental research methods (Non Design) One Group Pretest-posttest means the research only uses one class an experiment without a comparison class or control class. The population of this study are all class IV students at UPT SDN 207 Gresik with a total of 39 participants educate. The influence of the Children Learning in Science (CLIS) model on abilities Students' critical thinking in the science and science subject on the topic of magnetic force was carried out using the T Test, namely it is known that the correlation coefficient value is 0.572 with the value significant of 0.000 because the Sig value. 0.000 < 0.05 then it can be said that there is relationship between pretest and posttest variables. So the Children's learning model Learning in Science (CLIS) has a positive effect on critical thinking skills students at UPT SDN 207 Gresik. Keywords: Children Learning in Science (CLIS) Model, Critical Thinking